Peran Perguruan Tinggi dalam Meningkatkan Kesadaran Orangtua terhadap Kesehatan Mental Anak di Perumahan Babatan Pilang, Wiyung, Surabaya - Setyowati, Peni Jati; Ria Tri , Vinata; Masitha Tismananda, Kumala (PENITI BANGSA (Pemanfaatan Ilmu Pengetahuan dan Teknologi bagi Masyarakat), 2024)
Children's mental health is an important aspect that parents need to pay serious attention to. Awareness of the importance of mental health is often still low among parents. suicide cases are increasing. Economic demands, disharmonious families, problems with partners and problems at school are some of the many reasons someone ends their life. Suicide is the second highest cause of death in the 15-29 year age range. This condition shows that maintaining mental health in teenagers is important. In an effort to prevent or minimize the legal problems faced by society at this teenage age, the Faculty of Law, Wijaya Kusuma University, Surabaya is here to provide knowledge. The Faculty of Law, Wijaya Kusuma University, Surabaya as a university is a place for the development of science and technology and considering its existence in society, universities have an obligation to convey their knowledge to the community through community service activities in order to provide benefits to the wider community in general. This research aims to explain the role of parents in increasing awareness of children's mental health through a community service initiative. This initiative involves collaboration between higher education institutions and local communities to provide education and information resources to parents.